Chloroplast genetic engineering - Daniell, Henry (Henry Stewart Talks, 2007)
Advantages, concepts and methodology, Maternal inheritance and cytoplasmic male sterility, Agronomic traits to confer insect, herbicide, disease resistance, drought and salt tolerance and phytoremediation, Transformed crop species, Production and functional evaluation of human blood proteins (interferon) and vaccines (anthrax), Mechanism of oral delivery and protection against insulitis in non-obese diabetic mice, Crop chloroplast genomics